2007
DOI: 10.1203/pdr.0b013e318123fbcc
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability: Impact of Differences in Outlier Identification and Management Strategies on Common Measures in Three Clinical Populations

Abstract: Heart rate variability (HRV) is reported increasingly in pediatric research, but different strategies used to identify and manage potential outlier beats impact HRV parameter values in adults and animals. Do they in pediatrics? To compare the impact of different strategies to identifying and managing outliers, we used interbeat interval (IBI) data from three different populations: 10 stable premature infants, 33 stable pediatric oncology patients, and 15 healthy adults. Five commonly reported HRV parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 54 publications
0
38
0
1
Order By: Relevance
“…A filtered signal was obtained by applying a moving average filter with a 1000 sample window to the original RR sequence and identified outliers were replaced with the value of the corresponding sample in the filtered RR sequence (Kemper et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…A filtered signal was obtained by applying a moving average filter with a 1000 sample window to the original RR sequence and identified outliers were replaced with the value of the corresponding sample in the filtered RR sequence (Kemper et al, 2007). …”
Section: Methodsmentioning
confidence: 99%
“…Ectopy removal or replacement is shown to be essential regardless of the spectral estimation technique (Clifford & Tarassenko, 2005). Although the method used to handle erroneous RRIs have been shown to variously affect HRV estimates, a recent study, using pediatric and adult HR data showed that while the identification of outliers has an important impact, their handling (i.e., either dropping outliers or interpolation) had no impact on the estimation of HRV (Kemper et al, 2007). Time domain measures, like standard deviation of normal-to-normal intervals (SDNN) was least affected by editing methods (<5% error), although frequency domain measures were affected (Salo et al, 2001)…”
Section: Methodsmentioning
confidence: 99%
“…where RR i is i th sample of the tachogram, Average 100 and Std 100 are the mean and SD values of the previous 100 samples without outliers, and then they were replaced with the value of the corresponding sample of the smoothed signal (Kemper et al, 2007). …”
Section: Methodsmentioning
confidence: 99%